LOWEST EXCITED STATES REORDERING IN (ARENE)M(CO)3, WHERE M = Cr or W, COMPLEXES - Agus Abhi Purwoko; Alistair J. Lees (Indonesian Journal of Chemistry, 2009)
A series of electronic spectral changes was observed when (arene)M(CO)3 complexes (where arene = benzene, chlorobenzene, phenyltrimethylsilane, acenaphthene, mesitylene, and M = Cr or W) were irradiated with 313 nm light in benzene solution at 298 K in the presence of excess pyridine. These photolysis were neatly leading to the formation of (arene)M(CO)2(py) without any interference from further net photoreaction or thermal reaction on the same time scale. The lower photoreactivity was exhibited by acenaphthene complex. The influences of ring substituents in these complexes and of entering ligands on their photoreactions are discussed in detail with respect to reordering of their electronic states.